Chemical speciation of RhIII complexes in acidic, halide-rich media by means of 103Rh NMR spectroscopy : the importance of speciation in the selective separation and recovery of rhodium - Geswindt, Theodor Earl (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.